Brachiocephalic Vein Stenosis in Systemic Sclerosis - Sargın, Betül (European Journal of Therapeutics, 2022)
Systemic sclerosis (SSc) is a rare disease characterized by widespread collagen deposition resulting in fibrosis.1 In the literature, central retinal vein occlusion (CRVO)2-3 and subclavian vein thrombosis4 were reported as venous involvement in SSc.